P285 Beyond Care Bundles: The Development of a Structured Admission Model. (19th November 2012) - Thompson, C; Robinson, A; Duncan, P
Abstract : Hospital admission for acute respiratory disease accounts for 40% of the cost of managing respiratory disease in the UK. Data from national and European respiratory audits suggest the quality of care received is highly variable, and in the UK only 50% of people admitted for exacerbation of COPD will be managed by respiratory physicians. Admission to hospital is a significant event for someone with respiratory disease and represents an opportunity for the patient to receive a comprehensive and high quality respiratory review and interventions. Through project work with five project sites a structured admission model was developed and implemented through service improvement and process redesign. The components of the model include: Appropriate and timely (within 3 hours of admission) access to non-invasive ventilation (NIV) Access to respiratory specialist within 24 hours Proactive identification and management of high impact service users Ensuring every patient receives the key aspects of care during their admission (e.g. smoking cessation, inhaler technique cheque, self management plan) Ensure patients whose admission is their first presentation receive a quality assured diagnosis Ensure medicines optimisation during the in-patient stay Ensure every patient who has an admission for exacerbation of COPD has active follow-up and case management. Ensure every patient admitted for exacerbation of COPD receives pulmonary rehabilitation following discharge. Many of these principles have long been accepted as best practise in respiratory care however the limited adoption of these factors indicates that barriers to implementation still exist. The project sites demonstrated that care bundles and checklists can be an effective way of achieving elements of the structured admission model with up to 80% of COPD admissions being managed through a care bundle approach. In addition the effective prioritisation of workloads to better match case load and demand on the service allowed more patients to receive high quality care and increased job satisfaction for staff. The achievement of high quality care for all patients requires organisational change and an integrated systems approach within hospital organisations.